PENGEMBANGAN USAHA KERAJINAN BULO BATTI DI DESA ALLAERE - Lebang, Paulus; -, Chahyono (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Allaere village Tanralili district's districts have Bulo plantation crops Batti 'the bamboo is unique and has not been used optimally. On its uniqueness bamboo craftsmen